Supra-Versus Submaximal Cycle Ergometer Verification of VO2max in Males and Females - Brandon J. Sawyer; Nicholas McMahon; Kirsten L. Thornhill; Brett R. Baughman; Jenny M. Mahoney; Kai L. Pattison; Kaitlin A. Freeberg; Ryan T. Botts (MDPI AG, 2020)
This study was designed to determine the optimal intensity for verification phase testing (VP) in healthy, young adults. Thirty one young, active participants (16 females) completed a cycle ergometer graded exercise test (GXT) VO2max test and 4 VP tests at 80, 90, 100, and 105% of the maximum wattage achieved during the GXT. GXT and VP VO2max values showed a significant test x sex interaction (p = 0.02). The males elicited significantly higher VO2max values during the GXT, 80%, and 90% when compared to the 105%, (105 vs. GXT: p = 0.05; 105% vs. 80%: p < 0.01; 105% vs. 90%: p = 0.02). There were no significant differences in VO2max across the tests in the females (p > 0.05); 80% of the males achieved their highest VP VO2max during a submaximal VP test compared to only 37.5% of the females. A secondary study conducted showed excellent reliability (ICCs > 0.90) and low variation (CVs < 3%) for the 90% VP. Our findings show that a submaximal verification phase intensity is ideal for young healthy males to elicit the highest VO2max during cycle ergometer testing. For females, a range of intensities (80-105%) produce similar VO2max values. However, the 80% VP yields an unnecessarily high time to exhaustion.